PENDIDIKAN DALAM PERSPEKTIF SPIRITUAL - Hadi, Abdul (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2015)
The idea of spirituality in Islamic education is not a new idea. But the facts about the dichotomy between science and the science world hereafter impact on the education system. Therefore, it becomes very necessary in order not to lose the spirit of education. Spiritualize education in this paper is defined as a concept, the education system which not only intellectual and emotional side, but also education that emphasizes the spiritual or spiritual development capability with a standard that can be perceived by the learners to achieve the perfection of life according to Islamic size. The education Spirituality instill spiritual values for all components of education ranging from components educators, learners, educational, educational facilities, as well as the contents of the curriculum or the educational leadership.